In vitro organogenesis through nodal shoot segments to produce virus-free (Passiflora edulis f. flavicarpa) cv Qinmei#9 plants - Saneya Batool; Syed Mohsin Raza Bukhari; Peng Ling; Anam Zahid; Fozia; Ehab A. A. Salama; Abdulwahed Fahad Alrefaei; Mikhlid H. Almutairi; Mohamed A. A Ahmed (Cogent Food & Agriculture)
Yellow passion fruit (Passiflora edulis f. flavicarpa) is valuable edible specie with economic significance in China. Passion fruit faces yield losses due to viral diseases. This study used tissue culture of nodal shoot segments to propagate virus-free plants. Surface-sterilized nodal shoot segments were used and shoots were initiated on Murashige and Skoog (MS) medium supplemented with various concentrations of 6-Benzyladenine (6-BA) (0.0, 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 mg L−1). Multiple shoots were initiated (5.2 ± 1.09 shoots/explant) with a 6-BA concentration of 2.0 mg L−1. Sub-culturing of these multiple shoots on MS medium augmented with 2.0 mg L−1 6-BA and 0.2 mg L−1 IAA was successful in vitro with maximum numbers of shoots (6.6 ± 1.17) within four weeks of incubation. These regenerated shoots were assayed for presence of passion fruit woodiness virus (PWV) using enzyme-linked immunosorbent assay (ELISA); only virus-free shoots were used for further propagation. Root formation was very good in each indole-3-butyric acid (IBA) and (IAA) at a concentration of 0.6 mg L−1 with a maximum number of roots (7.2 ±1.30). Rooted plantlets were gradually acclimatized in a greenhouse and successfully established in soil. Thus, virus-free plants can be successfully regenerated directly from nodal shoot segments.